Bahan Ajar Matematika Kontekstual: Flipbook, Liveworksheet, Youtube - Ikashaum, Fertilia; Sulastri, Wahyuni; Azizah, Isnaini Nur (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2022)
This study aims to produce interactive digital teaching materials. The teaching materials are in the form of flipbooks that are integrated with live worksheet and youtube applications and are presented online to students via links. This research is motivated by the lack of teaching materials that are suitable for learning in the pandemic period and the lack of learning activities that involve students to actively participate in finding mathematical concepts. Many teachers do not have teaching materials because they follow the learning system from home. As a result, students also do not have a guide to study the material independently so that teachers and students alike have difficulty in carrying out the learning process. Therefore, to help students understand the material with a series of daily activities that can be done at home, students are given teaching materials that can be accessed independently. This research is a design research with the type of development study. The subjects of this study were seventh grade students of SMPT IT Ar Raihan Bandarlampung. The results showed that the teaching materials developed had met the valid criteria based on the validator's assessment and showed a potential effect as seen from the percentage of student learning completeness which was more than 70%.